The auditory environment of the young child - Abramovitz, Arnold (Department of Psychology, 2016)
The basic aim of this study is to explore the nature and development of the child's ability to perceive, understand and interpret auditory stimuli from which ordinary linguistic cues have been eliminated or in which they have been severely reduced. The term "non-linguistic" as it will be used here needs clarification. It refers to the use of any acoustic material except the conventional vocal symbols of everyday speech. Thus, it does not exclude human vocalizations as such, but only those which carry the semantic content of the language of the individual or subject. Confusion is possible over this issue because of the wide definition of language currently held. Thus the first definition supplied by English and English (1958) is "any form of intercommunicative behaviour, verbal or non-verbal". To demarcate our area of interest more precisely it is necessary to attempt an a priori classification of the total acoustic environment of an individual of a given language and culture.